Upper airway anomalies in children: From diagnosis to treatment - Serio, Paola; Colosimo, Denise; Baggi, Roberto; Avenali, Stefano; Mussi, Nicole; Bertelli, Luca; Esposito, Susanna; Majori, Maria; Corbetta, Lorenzo; Fainardi, Valentina (Acta Biomedica Atenei Parmensis, 2024)
Endoscopy of the airways plays a crucial role to investigate respiratory symptom and signs in newborns and children. Upper airway anomalies include malformations and acquired conditions found from the nose to the larynx. Common anomalies of the upper airways include laryngomalacia, vocal cord paralysis and subglottic stenosis. In the child their clinical presentation is often characterized by dysfunction in breathing, feeding or phonation. Most severe cases of congenital anomalies can present with respiratory distress at birth. Endoscopy is important not only for detection and diagnosis but also for treatment that is tailored to each condition depending on disease and severity. This review describes the commonest congenital or acquired anomalies of the upper airways seen in children.